Bicuspid aortic valve sparing root replacement. Issue 1 (22nd November 2020) - Patel, Parth M.; Wei, Jane W.; McPherson, LaRonica; Binongo, Jose; Leshnower, Bradley G.; Chen, Edward P.
Abstract: Background and Aim of Study: Mid and long‐term data regarding the durability of bicuspid aortic valve sparing root replacement is not completely understood. In this study, our institutional experience is reviewed regarding this procedure with special attention to the operative technique. Methods: From 2004 to 2019, 1241 patients underwent aortic root replacement and of these 79 patients underwent bicuspid aortic valve sparing root replacement. Early and late outcomes along with echocardiographic data were reviewed. Univariate analysis was used to identify risk factors for mortality. Results: Median age at operation was 43 (inner quartile range: 34.5–50.5) years, with 17% (14) being female. Median follow up time was 4 (inner quartile range: 1–8) years with 359 years of total follow up. Early mortality was 2.5% (2). Overall 10‐year freedom from aortic valve intervention was 95.6%. Risk factor analysis did not demonstrate preoperative root diameter, aortic diameter, or aortic insufficiency to be risk factors for mortality. Conclusion: Bicuspid aortic valve sparing root replacement can be performed safely in the setting of aortic root pathology and valve insufficiency. With appropriate selection and excellent surgical technique, long‐term durable valve function is observed without the need for repeat valve intervention.